Performance of the 2011 ACR/EULAR preliminary remission criteria compared with DAS28 remission in unselected patients with rheumatoid arthritis - Thiele, K.; Huscher, D.; Bischoff, S.; Spathling-Mestekemper, S.; Backhaus, M.; Aringer, M.; Kohlmann, T.; Zink, A.; German Collaborative Arthritis, Centres (Ann Rheum Dis, 2013)
OBJECTIVE: To compare the performance of the preliminary American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) remission criteria with the 28-joint count Disease Activity Score (DAS28) remission in unselected ’real-life’ patients. METHODS: Remission was calculated according to the DAS28 and to both versions of the ACR/EULAR criteria (Boolean or Simplified Disease Activity Index (SDAI)-based) for 6864 patients with rheumatoid arthritis (RA) who were enrolled in the national database of the German Collaborative Arthritis Centres between 2007 and 2009. Logistic regression analyses identified factors that were responsible for patients in DAS28 remission to miss the new criteria. In addition, the functional status of patients who fulfilled the different remission criteria was compared with that of an age- and sex-matched population sample. RESULTS: Of all patients, 28% were in DAS28, 7% in Boolean and 11% in SDAI remission. Of those in DAS28 remission, 21.0% were also in Boolean and 34% also in SDAI remission. Higher scores for pain and fatigue, the presence of degenerative spine disease, longer disease duration and male gender were significantly associated with missing the new criteria despite being in DAS28 remission. Compared with age- and sex-matched samples from the general population, patients in DAS28 remission had a similar functional ability while patients in remission according to the new criteria had better functional scores. CONCLUSIONS: Patients fulfilling the new remission criteria tend to be not only free from active RA, but also from other disabling diseases. If these criteria are applied in clinical practice to guide treatment decisions, the impact of comorbidity should be taken into account.